May Autogenous Grafts Increase the Effectiveness of Hyalonect Membranes in Intraosseous Defects: An Experimental In Vivo Study - Caner Yilmaz; Selim Ersanli; Murat Karabagli; Vakur Olgac; Nilufer Bolukbasi Balcioglu (Medicina, 2021)
Background and Objectives: Guided bone regeneration (GBR) surgeries are used for dental implant placements with insufficient bone volume. Biomaterials used in GBR are expected to produce sufficient volume and quality of bone swiftly. This study aims to histologically evaluate the effectiveness of the use of Hyalonect membranes alone or with autogenous grafts in intraosseous defects. Materials and Methods: This study is an experimental study on sheep. Surgeries were performed under general anesthesia in accordance with ethical rules. Five 10 mm defects were surgically created in each ilium of six sheep. One defect was left empty in each ilium (group ED). The defects in the experimental group were covered with Hyalonect membrane while unfilled (group HY) or after being filled with autogenous bone grafts (ABG) (group G+HY). In the control group, the defects were either covered with collagen membrane while unfilled (group CM) or after being filled with the ABG group (G+CM). The sheep were histologically and histomorphometrically evaluated after being postoperatively sacrificed in the third and sixth week (three animals in each interval). Results: All animals completed the study without any complications. No difference was found between groups in the third and sixth weeks regarding the inflammation, necrosis, and fibrosis scores. The G+CM (52.83 ± 3.06) group was observed to have a significantly higher new bone formation rate than all the other groups in the third week, followed by the G+HY group (46.33 ± 2.25). Similar values were found for HY and CM groups (35.67 ± 4.55 ve 40.00 ± 3.41, respectively, p = 0.185), while the lowest values were observed to be in group ED (19.67 ± 2.73). The highest new bone formation was observed in group G+CM (82.33 ± 4.08) in the sixth week. There was no difference in new bone formation rates between groups G+CM, G+HY (77.17 ± 3.49, p = 0.206), and CM (76.50 ± 2.43, p = 0.118). The insignificant difference was found ED group and group HY (55.83 ± 4.92, 73.50 ± 3.27, respectively, p = 0.09). The residual graft amount in the G+CM group was found to be statistically significant at 3 weeks (p = 0.0001), compared to the G+HY group, and insignificantly higher at the 6th week (p = 0.4). Conclusions: In this study, close values were observed between G+HY and G+CM groups. Further experimental and clinical studies with different graft materials are required to evaluate the effectiveness of HY in GBR.